Why international human rights treaties fail to promote, Afghan women's empowerment; political participation - Mayar, Mohammad Nazeer (BRAC University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2021.